The Implementation of Circular Design Strategies at the Micro and Meso Levels: Evidence from Taiwan's Manufacturing Firms - Li , Ting-Yu; Lin , Pi-Jui; Sung, Tung-Jung (European Journal of Sustainable Development, 2025)
This study explores how circular design strategies are interpreted and applied at the micro and meso levels. Using a two-stage explanatory mixed-methods design. Stage 1 combined expert surveys and interviews to construct level-specific strategy frameworks, resulting in five strategies and 19 key items at the micro level, and six strategies and 24 key items at the meso level. In Stage 2, a questionnaire distributed to 60 Taiwan-based practitioners with circular design experience, revealed broadly aligned quantitative scores across levels, while qualitative insights exposed divergent implementation logic. Micro-level actors prioritized usability, modularity, and behavioral incentives, while meso-level respondents emphasized reverse logistics, system integration, and long-term infrastructure. These findings reflect role-based priorities shaped by daily practice and system responsibilities. This study offers a level-sensitive framework that clarifies how CDSs are evaluated and enacted across levels, providing theoretical insight and practical guidance for design, policy, and cross-level collaboration. Keywords: circular design, circular design strategies, system-level design, circular economy, sustainability